Comment to Hansson, S. et al. (2017): "Competition for the fish – fish extraction from the Baltic Sea by humans, aquatic mammals, and birds", with special reference to cormorants, perch, and pikeperch. (3rd May 2018) - Heikinheimo, Outi; Lehtonen, Hannu; Lehikoinen, Aleksi
Abstract: Hansson et al. (2017) concluded that competition between fisheries and piscivorous mammals and birds exists in the Baltic Sea, based on the estimation of biomass of the fish species consumed in the ICES subdivisions. We compared their results to the data and scientific knowledge from the coastal waters of Finland and show that local differences in fisheries, fish assemblages and abundance of predators should be taken into account to reliably assess potential competition. Hansson et al. (2017) did not include the piscivorous fish in their analysis, but these may be the most important predators. In the Archipelago Sea, for instance, the consumption by fish predators is considerably larger than that of cormorants.